Diagnosing low back pain in an evidence-based way: How accurate are we? - Rilind Shala (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Back pain is the leading cause of disability globally with 818,000 disability-adjusted life 51 years estimated to be lost annually due to work-related Low Back Pain (LBP) [1].